Attitude Towards Language Use In Digital - Rahmila Rahmila (Universitas Islam Negeri Antasari Banjarmasin, 2015)
The development of information communication technology (ICT) and digital media has enabled people to communicate with each other in a more sophisticated way. This research was conducted to find out the attitude of students toward digital communication and the attitude of lecturers toward digital communication compared to that of students. This research used a quantitative approach with cross-sectional survey design.The research participantswere 112 student of English Department Faculty of Tarbiyah and Teacher Training and 22 lecturers who teach at English Department and Language Service Center IAIN Antasari Banjarmasin. Data were collected through questionnaire which consists of 28 item statements using Likert scale and 3 open-ended questions.The findings reveal that students and lecturers are familiar with the use of language features in digital communication such as abbreviation, acronyms, and emoticons. They agree that language use in digital communication is innovative and creative. However, the majority of respondents think that awareness toward audience and context is very important so we should use language style appropriately. Key words: Digital Communication, Language Use, AttitudePerkembangan teknologi komunikasi dan informasi dan media digital memungkinkan orang untuk dapat saling berkomunikasi denngan sesama dengan lebih canggih. Penelitian ini bertujuan untuk mengetahui sikap siswa terhadap komunikasi digital dan membandingkannya dengan sikap dosen terhadap komunikasi digital. Penelitian ini menerapkan pendekatan kualitatif dengan desain survey silang. Responden penelitian adalah 112 mahasiswa Jurusan Pendidikan Bahasa Inggris Fakultas Tarbiyah dan 22 dosen yang mengajar pada Jurusan Pendidikan Bahasa Inggris dan Pusat Pengembangan Bahasa (PPB) IAIN Antasari Banjarmasin. Data penelitian diperoleh melalui kuesioner yang terdiri dari 28 item yang disusun dalam skala likert dan tiga pertanyaan terbuka. Hasil penelitian menunjukkan bahwa para siswa dan dosen telah akrab dengan fitur-fitur bahasa yang digunakan dalam komunikasi digital seperti singkatan, akronim, dan emotikon. Mereka setuju bahwa penggunaan bahasa dalam komunikasi digital bersifat inovatif dan kreatif. Namun demikian, mayoritas respon den berpendapat bahwa kesadaran terhadap lawan bicara/pendengar dan konteks adalah hal yang penting sehingga kita perlu menggunakan gaya bahasa yang sesuai.Kata kunci: Kounikasi Digital, Penggunaan Bahasa, Sikap